Global research into cash transfers to prevent intimate partner violence - Palermo, Tia; Barrington, Clare; Buller, Ana Maria; Heise, Lori; Hidrobo, Melissa; Ranganathan, Meghna; Roy, Shalini (Elsevier, 2022)
We applaud Merike Blofield and colleagues (January, 2022)1 for highlighting the potential of cash transfer programmes to reduce intimate partner violence (IPV) in Latin America during the COVID-19 pandemic. On the basis of our research in Latin America and other regions, we argue that the potential of cash transfers to reduce IPV is relevant globally. We also note important nuances to the points made by Blofield and colleagues, some of which are particularly relevant for other regions where the prevalence of IPV is highest.